A history of interior design - Pile, John F. (Hoboken, N.J. : John Wiley & Sons, 2021)
A History of Interior Design tells the story of 6,000 years of domestic and public space. It's an essential resource for students, professionals and anyone interested in interior design, the decorative arts, architecture and art history."
Includes bibliographical references and index.
Keywords: Interior decoration -- History; Interior architecture -- History; Print books